Communication and Collaboration Ability Through STEAM Learning Based Project Based Learning (PjBL) Grade V Elementary School - Abu Dharin; Indah Ayu Lestari; Siswadi Siswadi (Postgraduate, University of Mataram, 2023)
The aim of this research is to find out if there is an increase in communication and collaboration skills in learning using the STEAM approach based on Project Based Learning (PjBL) for fifth grade elementary school students. The method used is field research with a qualitative approach. The results of the study show that learning using the STEM-based project-based learning approach can improve students' soft skills, especially in the communication and collaboration skills of fifth grade elementary school students. STEAM is a new knowledge that is rarely used by teachers in learning. PjBL-based STEAM can develop students' communication and collaboration skills to adapt to 21st Century developments. MIM Patikraja, Patikraja District, Banyumas Regency is one of the madrasas that implements PjBL-based STEAM learning in teaching and learning activities that have a positive impact. Among them, in addition to learning to be creative and fun, MIM Patikraja students and teachers often make achievements in various fields of competition. Because students and teachers are used to establishing good communication and collaboration. In addition, STEAM teaches students and teachers to be literate in technology so as to facilitate the learning process